Effect of Compound (NPS) Fertilizer Type on Yield and Nutrient Use Efficiency of Maize (Zea mays L.) at Beko Village in Yeki District, Southwest of Ethiopia - Wedajo, Mulisa; Kidanu, Selamyihun; Reggasa, Alemaheyu (Discoveries in Agriculture and Food Sciences, 2022)
Farmer in different part of Ethiopia use similar type of fertilizer and amount that below the crop requirements, even the low soil fertility which limit the crop production as a general. To solve the over-blanket fertilizer application over different agro-ecology Ethiopian Soil Information System (EthioSIS) mapping the soil fertility and recommended types of fertilizer for specific location. The NPS type of fertilizer where recommended for Beko village, but the rate of this fertilizer type was not studied so far. So, this field experiment was conducted to determine the rate of NPS fertilizer type and nutrient use efficiency of maize during the 2018 cropping season at Beko village. A total of eight treatments with four replications were laid out in a factorial randomized complete block design. Treatments were control (zero fertilizer), previously recommended nitrogen and phosphorus (92 kg N/ha + 30 kg P/ha), 150NPS +100 urea +100 K2O kg/ha, 200NPS +100 urea + 100 K2O kg/ha, 250NPS +100 urea +100 K2O kg/ha, 150NPS +150 urea +100 K2O kg/ha, 200NPS +150 urea +100 K2O kg/ha, 250NPS +150urea +100 K2O kg/ha. Data was statistical analyzed by SAS and mean treatment difference were compared by list significant difference (LSD). As analysis of variance indicated that application of NPS fertilizer were not influenced plant height, ear height, ear length, cob length, number of ears per plant, thousand seed weight, harvest index, and shelling percentage as compared to the previously recommended NP fertilizer but grain and biomass yield were influenced except application of 150NPS +100 urea. Among the treatment application of 250 NPS + 100 urea gave the highest maize grain yield (8390.1 kg/ha). The Application of NPS fertilizer improved nitrogen and phosphorus use efficiency of maize as compared to the previously recommended NP. The highest N use efficiency (57.98 kg/ha) was obtained from the application of 250 NPS +100 urea, while the lowest N use efficiency (23.89 kg/ha) was from the previously recommended NP fertilizer. As economic analysis indicated the study conclude that application of 150 NPS +150 urea recommended for the study area.